1991
DOI: 10.1128/mcb.11.8.3931
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assembly of yeast mitochondrial alpha-ketoglutarate dehydrogenase complex.

Abstract: The assembly of a-ketoglutarate dehydrogenase complex (KGDC) has been studied in wild-type Saccharomyces cerevisiae and in respiratory-deficient strains (pet) with mutations in KGD1 and KGD2, the structural genes for a-ketoglutarate dehydrogenase (KE1) and dihydrolipoyl transsuccinylase (KE2) (20,36). This important enzyme of the tricarboxylic acid cycle has been isolated from mammalian sources (9, 27), from Escherichia coli (22), and from the yeast Saccharomyces cerevisiae (8). The eukaryotic and prokaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…By comparing expression profiles in response to defects in genes encoding different subunits of hetero-oligomeric TCA cycle proteins, it was possible to analyze how the cell responds to different defects in the same enzyme. Although isocitrate dehydrogenase and succinyl-CoA ligase require both subunits for activity, subcomplexes composed of only some subunits of ␣-ketoglutarate dehydrogenase complex and succinate dehydrogenase can be detected (Repetto and Tzagoloff, 1991;Scheffler, 1998). However, cluster analysis suggested that the responses to defects in genes encoding different subunits of the hetero-oligomeric TCA cycle enzymes were, for the most part, very similar (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing expression profiles in response to defects in genes encoding different subunits of hetero-oligomeric TCA cycle proteins, it was possible to analyze how the cell responds to different defects in the same enzyme. Although isocitrate dehydrogenase and succinyl-CoA ligase require both subunits for activity, subcomplexes composed of only some subunits of ␣-ketoglutarate dehydrogenase complex and succinate dehydrogenase can be detected (Repetto and Tzagoloff, 1991;Scheffler, 1998). However, cluster analysis suggested that the responses to defects in genes encoding different subunits of the hetero-oligomeric TCA cycle enzymes were, for the most part, very similar (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The lpd1 mutant 53.1.4 that is defective in lipoamide dehydrogenase produced wildtype levels of 2-phenylethanol. Lipoamide dehydrogenase is an essential component of branched-chain ␣-ketoacid dehydrogenase, pyruvate dehydrogenase, ␣-ketoglutarate dehydrogenase, and glycine decarboxylase (13)(14)(15)(16). Hence, because strain 53.1.4 lacks branched-chain ␣-ketoacid dehydrogenase, it can be concluded that this activity is not involved in the formation of 2-phenylethanol from phenylalanine.…”
Section: Resultsmentioning
confidence: 99%
“…The overall KGDHC activity is reduced when KGDHC is assembled in the presence of excess of E2k (46). Whereas in the absence of E2k, separated dimeric E1k and E3 are detected, activity was not measured (45). The possible existence of heterogeneous quaternary structures of ␣-ketoacid dehydrogenase complexes (47)(48)(49)(50) implies the potential flexibility in subunits composition of KGDHC and its response to challenges.…”
Section: E2k Depletion and Cell Functionmentioning
confidence: 99%
“…Some relevant studies in yeast have tested the responses of the other two subunits and assembly in the absence or in the presence of excess of E2k (39,(45)(46). However, these studies were only with a total deletion of E2k or overexpression.…”
Section: E2k Depletion and Cell Functionmentioning
confidence: 99%